The greater calorie deficit applied to the bodybuilding athlete, the greater their loss of fat-free mass on the stage presentation? - Haniel Fernandes (Clinical Nutrition Open Science, 2023)
Summary: Background & Aims: The total preparation for a bodybuilding competition basically involves two phases, the preparation phase, and the pre-competition phase, in which both tend to add up on average 32 weeks. During the pre-contest phase, bodybuilding athletes maintain a negative energy balance both by lower energy intake from the diet and by the longer time dedicated to training, to try reducing the body fat percentage, fat-free mass (FFM) maintenance and to present a dense and dry physique on stage in the competition day. Therefore, this work tries to bring a correlation explanation between a greater caloric deficit applied to the bodybuilding athlete during his preparation with the variation in fat free mass between the preparation and pre-contest phases. This way, open the question: “could greater caloric deficits in the bodybuilding athlete's dietary intake be closely correlated with negative changes in fat-free mass for stage performance?” Methods: The author searched PubMed and ScienceDirect databases for recent studies involving the food consumption of bodybuilders when preparing for competition using the keywords “bodybuilding”, “diet” and “preparation”. 16 results were obtained from ScienceDirect and 8 from PubMed. Two cross-sectional studies and two case studies involved the evaluation of the food consumption of forty-four male athletes practicing bodybuilding over eighteen years of age during their preparation that lasted from 5 to 32 weeks. Participants' diet was monitored by self-report. The studies were selected and observationally evaluated by the author regarding the size of the variation in the energy intake and its possible correlation with the variation in the fat-free mass from the beginning of the preparation until the day of the competition. Results: Of the four studies, the greatest average variation in energy intake (final minus initial) exceeded 1700 kcal and the smallest did not reach even 300 kcal. On the other hand, the study with the longest preparation time had the greatest loss of body weight even without applying the greatest energy variation between the studies in table 1 yet had the greatest fat-free mass loss with a worse result than the study with the shortest preparation time. Conclusions: Observationally, higher caloric deficits in the bodybuilding athlete's food intake cannot closely correlated with negative changes in fat-free mass for the stage presentation.